Analisis Sistem Akuntansi Penggajian ASN pada Kantor Camat Medan Johor - Iswin Syukur Nasution; Ratna Sari Dewi; Indra Fauzi; M.Rizaldy Wibowo (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
This study aims to analyze the implementation of the payroll accounting system at the Medan Johor District Office, focusing on the system’s effectiveness, the roles of the treasurer, Commitment-Making Officer (PPK), and Budget User Officer (PA), as well as the challenges encountered. A descriptive qualitative approach was employed using interviews, observation, and documentation. The findings reveal that the payroll system utilizes the Regional Government Information System (SIPD) with disbursement through SISKA. The system is considered effective due to the use of non-cash payments and a layered verification mechanism. However, several challenges remain, including payroll delays caused by late disbursement of budget allocation (SPD), data entry errors in attendance and e-performance, and the lack of integration between the attendance system and payroll. The study concludes that while the payroll system is relatively effective, improvements in budget coordination, system integration, and staff training are necessary to enhance accuracy and efficiency.